Upaya Meningkatkan Motivasi dan Hasil Belajar Matematika Menggunakan Bantuan Buku Saku Perkalian Kelas V SDN 26 Ampenan - Saidah, Safinah Tulhariya; Makki, Muhammad; Makki, Habibi (Mataram University, 2025)
Based on the results of the research conducted, it can be concluded that the use of a multiplication pocket book can improve learning outcomes and motivation among fifth-grade students at SDN 26 Ampenan. The findings showed that the students’ average score increased from 55.00 (pre-test) to 70.00 (Cycle I) and 85.00 (Cycle II), while the percentage of students achieving the minimum mastery criteria (KKM) rose from 40% to 90%. In addition, 85% of the students reported feeling more confident and motivated in learning mathematics. Therefore, the multiplication pocket book has proven to be an effective and practical learning medium that can enhance students’ understanding of multiplication operations.